1999
DOI: 10.1128/aac.43.9.2138
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Enrofloxacin on Porcine Phagocytic Function

Abstract: The interaction between enrofloxacin and porcine phagocytes was studied with clinically relevant concentrations of enrofloxacin. Enrofloxacin accumulated in phagocytes, with cellular concentration/extracellular concentration ratios of 9 for polymorphonuclear leukocytes (PMNs) and 5 for alveolar macrophages (AMs). Cells with accumulated enrofloxacin brought into enrofloxacin-free medium released approximately 80% (AMs) to 90% (PMNs) of their enrofloxacin within the first 10 min, after which no further release w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…A plasma concentration of 0.1 g/ml was considered therapeutically adequate, which is the MIC value of enrofloxacin against some common veterinary pathogens [36][37][38]. The long post-antibiotic effect of enrofloxacin can prevent bacterial re-growth even when plasma and tissue concentrations decrease below MIC [39]. The plasma enrofloxacin concentration in SLN groups maintained over the minimum therapeutic concentration for a long time and was below MIC for a persisted period, especially in the tetradecanoic acid-SLN and palmitic acid-SLN groups.…”
Section: Discussionmentioning
confidence: 99%
“…A plasma concentration of 0.1 g/ml was considered therapeutically adequate, which is the MIC value of enrofloxacin against some common veterinary pathogens [36][37][38]. The long post-antibiotic effect of enrofloxacin can prevent bacterial re-growth even when plasma and tissue concentrations decrease below MIC [39]. The plasma enrofloxacin concentration in SLN groups maintained over the minimum therapeutic concentration for a long time and was below MIC for a persisted period, especially in the tetradecanoic acid-SLN and palmitic acid-SLN groups.…”
Section: Discussionmentioning
confidence: 99%
“…This effect may help to explain why the pigs treated with enrofloxacin did not seroconvert. It has also been shown that the killing of A pleuropneumoniae by alveolar macrophages and polymorphonuclear leucocytes is enhanced by enrofloxacin (Schoevers and others 1999). …”
Section: Discussionmentioning
confidence: 99%
“…on humoral immunity in humans has been reported after ciprofloxacin treatment (Williams et al, 2005). However, enrofloxacin may lead to an increase in the bactericidal action of phagocytes, such as neutrophils, in pigs (Schoevers et al, 1999). It has also been shown that after enrofloxacin administration the number of lymphocytes in the peripheral blood of 17-d-old chickens was significantly higher than that in the control group (Fleischer et al, 2000).…”
Section: Introductionmentioning
confidence: 94%